The Effects Of Varying Protein Levels On The Growth, Survival And Yield Of Penaeus Indicus Under Iranian Condition - Jahromi, Abdulhamid Yazdani (1995)

(untitled)
Four shrimp diets for Penaus indicus were formulated using available indigenous feed ingredients (fish meal, shrimp meal, soybean meal, wheat flour, corn flour and corn oil ) using linear programming techniques All the diets were isocaloric ( 400 kca1/100g ), containing 5 to 115% fat The dietary protein levels were 30, 35 , 40 and 45% with an amino acid profile similar to that of the prawn The production costs of the diets were Rials 1140, Rials 1240, Rials 1340 ,Rials 1440 per kilogram respectively Eighteen indoor concrete tanks ( 345 m2 each) receiving flow-through seawater (42 ppt) of 21 /sec were stocked With 138 P. indicus fry (0014 g mean wt ) at a stocking density of 40 shrimp per m2 In the case of the pond, eighteen compartments (95 m 2 each ) separated by nylon nets in pond were also prepared and stocked with 380 shrimps of the same size and stocking density as the tank experiment The shrimps were fed with the prepared diets and two commercial diets as a control for growth, feed and protein utilisation, and carcass composition during grow-out for 115 days Specific growth rate (SGR) was high for all diets with a mean ranging from 302 to 318 With the exception of a commercial feed (Chinah) which had a value of 081 There were no significant differences (P> 0 05) among diets for growth rate, final length, fat and protein deposition in tanks and pond Significant differences (P<0 05) were observed in shrimp fed 40% protein diet for net profit, yield, survival rate and weight gain as compared to shrimp fed the other diets The results also indicate that shrimp P.indicus can be reared in sea water of high salinity from fry through marketable sizes more economically on an optimum dietary protein of 40%